THE EFFECTIVENESS OF CYCLOOXYGENASE-2 INHIBITORS AND EVALUATION OF ANGIOGENESIS IN RAT COLORECTAL CANCER MODEL - Gungor, Hilal; Ilhan, Nevin; Ilhan, Necip (Int Inst Anticancer Research, 2014)
[Abstract Not Available]